The influence of perceived design source (AI vs. human) on Chinese consumers’ purchase intention: The mediating roles of novelty, perceived brand effort, and product type - Yunxi Feng; Yibei Ran (PLoS ONE, 2026)
Product design is a crucial source of competitive advantage for companies and greatly influences their market position. Information about “who designed the product,” known as the perceived design source, is gaining widespread attention in product design communication. Due to limitations in existing research, this study, based on 316 valid questionnaires, used Mplus 8.0 to examine how the perceived design source (AI versus human) affects Chinese consumers’ purchase intentions. The research findings are as follows: (1) Consumers are more willing to buy products perceived as designed by AI compared to those designed by humans; (2) Novelty mediates the relationship between the perceived design source and consumers’ purchase intentions; (3) Perceived brand effort also mediates this relationship; (4) Product type moderates the relationship between the perceived design source and purchase intentions. These conclusions not only advance marketing theory but also help businesses develop targeted marketing strategies and increase consumer purchasing.